2020
DOI: 10.1007/s00432-020-03241-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic versus nuclear THR alpha expression determines survival of ovarian cancer patients

Abstract: Purpose Thyroid hormone receptors (THR) have manifold functions and are involved in the carcinogenesis of several tumor types. Within this study, we aimed to investigate the expression pattern (nuclear versus cytoplasmic) of the THR alpha and its impact on patients survival in ovarian cancer (OvCa). Methods The presence of the thyroid hormone receptors THRα, THRα1 and − 2 was investigated in 156 ovarian cancer samples using immunohistochemistry (IHC) using semi-quantitative immunoreactivity (IR) scores and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…However, recent data on other nuclear receptors in cancer research indicate that the prognostic value of nuclear receptors depends on their subcellular localization [24]. Consistently with our findings, Ditsch et al demonstrated that there is a direct link between the nuclear localization of THR and increased OS in epithelial ovarian cancer [22]. However, THR has been identified to show cancer-promoting activities during BC development [24].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, recent data on other nuclear receptors in cancer research indicate that the prognostic value of nuclear receptors depends on their subcellular localization [24]. Consistently with our findings, Ditsch et al demonstrated that there is a direct link between the nuclear localization of THR and increased OS in epithelial ovarian cancer [22]. However, THR has been identified to show cancer-promoting activities during BC development [24].…”
Section: Discussionsupporting
confidence: 90%
“…NRs are activated by binding to lipophilic metabolites and mainly function as transcription factors in the nucleus [19,20]. Novel literature demonstrates that, besides the well-established NR, other receptors, including the retinoid X receptor (RXR), thyroid hormone receptors (THRs) and vitamin D receptor (VDR), play a significant role in the pathophysiology not only of BC but also of other cancer entities [21][22][23]. Studies on the role of NR in distinct intracellular compartments indicate a specific prognostic value, depending on the subcellular localization [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, our study raised an interesting issue of localization of IHC staining. In previous studies of ovarian cancer, different localizations of thyroid hormone receptors and αvβ3 integrin demonstrated different nuclear and non-nuclear signaling pathway for cancerogenesis [ 40 , 41 ]. The translocation of transmembrane proteins from the cell membrane to the nucleus may be another crucial mechanism [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was found that the presence of Gd was indicative of a better prognosis in endometrial cancer whereas the presence of the immunosuppressive Gd-A indicated a poorer overall survival rate ( Lenhard et al, 2013 ). In ovarian cancer too, the presence of Gd-A has a positive correlation with other markers that indicate a poorer outcome ( Scholz et al, 2012 ; Ditsch et al, 2020 ). The presence of Gd can be detected by immunohistological staining of tissue biopsies and also in serum samples but is just one of many proposed neoplastic markers, the clinical significance of which, if any, as a cancer marker remains to be established.…”
Section: Glycodelinmentioning
confidence: 99%